Optimization of a portable ligand-free optical spectroscopy method for SARS-CoV-2 protein detection - Fatin Hamimi Mustafa; Nik Yusnoraini Yusof; Mawaddah Mohd Azlan; Fariza Hanim Suhailin; Chan Yean Yean; Nik Mohd Noor Nik Zuraina; Mohd Zulkifli Salleh; Hironaga Uchida; Irneza Ismail; Rosline Hassan; Raja Kamarulzaman Raja Ibrahim; Mohd Adzir Mahdi (Biosensors and Bioelectronics: X)
The rapid spread of COVID-19 has underscored the need for fast, portable, and reliable diagnostic tools. Conventional techniques such as polymerase chain reaction and emerging biosensors like surface plasmon resonance require complex procedures for ligand development and immobilization, which often involve probes, antibodies, or aptamers. This study proposes a ligand-free detection strategy based on optical spectroscopy for the rapid identification of the SARS-CoV-2 protein. The detection workflow includes two key phases: optimization and clinical validation. In the optimization phase, transmittance spectral measurements were conducted on SARS-CoV-2 protein to determine the optimal wavelength within the ultraviolet–visible–near infrared range (200–1100 nm). The most effective fiber configuration was also evaluated using three combinations of transmitter–receiver fiber diameters: 600–400 μm, 600–100 μm, and 200–400 μm. The optimal detection parameters were identified as 275 nm for wavelength and 600–400 μm for fiber configuration. Specificity testing confirmed complete discrimination between SARS-CoV-2 protein and other proteins, including SARS-CoV and rBmSXP, with 100 % specificity. Subsequently, clinical validation was conducted on 21 patients using the optimized parameters. Optical spectroscopy measurements were compared with real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR), yielding a correlation coefficient of 0.6038 with statistical significance (p < 0.01). These findings demonstrate the potential of portable, ligand-free optical spectroscopy for rapid SARS-CoV-2 detection at the point of care.